2018
DOI: 10.1680/jgeen.16.00138
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of a sandy soil by enzymatic calcium carbonate precipitation

Abstract: The effect of curing time, content of grout solution and concentration of urea, calcium chloride and urease enzyme on the process of enzymatic calcium carbonate precipitation was analysed. Initially, the process was studied in test-tube experiments by evaluating the amount of calcium carbonate precipitated using X-ray diffraction tests. The method was then applied to stabilise a sandy soil to examine the strengthening effect using unconfined compressive strength tests, X-ray diffraction and scanning electron m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(31 citation statements)
references
References 29 publications
2
29
0
Order By: Relevance
“…All the UCS tests were repeated twice (soil A) or three times (soils B, C and D). The amount of urease used (8 kU/L) were based on the results obtained by Carmona et al [13] for soil A.…”
Section: Testing Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…All the UCS tests were repeated twice (soil A) or three times (soils B, C and D). The amount of urease used (8 kU/L) were based on the results obtained by Carmona et al [13] for soil A.…”
Section: Testing Methodologymentioning
confidence: 99%
“…The few works about the use of enzymatic CaCO 3 precipitation in soils show that this process improves the strength, the stiffness [8][9]11] and decreases the permeability and the porosity of the porous media [7,8,10]. Although with high scattering, the results also show that the level of improvement increases with the amount of CaCO 3 precipitated [8,11,13].…”
Section: Introductionmentioning
confidence: 93%
“…B i o -c e m e n t a t i o n v i a E I C P p r ocesses may be affected by several parameters: pH, temperature, concentrations of cementation reagent (CCR) and urease concentration [17,18]. Among these factors, CCR is a critical parameter in improving the strength of bio-cemented soil.…”
Section: Introductionmentioning
confidence: 99%
“…Several EICP-related studies have shown contradictory results withregard to the optimal CCR resulting in the highest calcium carbonate content, which in turn leads to improved geomechanical properties of the soil. Some have shown that increasing CCR to a certain level has a detrimental effect on the precipitation of calcium carbonate [11,19], whereas others have reported the opposite [13,18] Dilrukshi and Kawasaki [9] evaluated the effect of CCR (CaCl 2 -urea), urease, and curing period on the unconfined compressive strength (UCS) of sandy soil; the findings have shown that the increase in curing period and CCR (0.3-0.7 M) resulted in an increase in the estimated UCS value from 500 kPa to 4 MPa, whereas the performance of low and high urease activity was more efficient at low and high CCR, respectively. The high strength obtained in the study when compared with others may be as a result of the testing method adopted to evaluate the unconfined compressive strength.…”
Section: Introductionmentioning
confidence: 99%
“…Carmona et al (2018) focus on an innovative soil improvement technique for granular materials based on artificially induced calcite precipitation, by mixing the soil with urea, calcium chloride and the urease enzyme. Given the complex (bio-)chemo-mechanical coupled effects brought about by this technique, laboratory experimentation is a fundamental step to understand the effectiveness of the method for practical purposes.…”
mentioning
confidence: 99%